Active DC voltage balancing PWM technique for high-power cascaded multilevel converters - Tarisciotti, Luca; Zanchetta, Pericle; Watson, Alan James; Bifaretti, Stefano; Clare, Jon C.; Wheeler, Patrick (Institute of Electrical and Electronics Engineers, 2014)
In this paper a dedicated PWM technique specifically designed for single-phase (or four wire three-phase) multilevel Cascaded H-Bridge Converters is presented. The aim of the proposed technique is to minimize the DC-Link voltage unbalance, independently from the amplitude of the DC-Link voltage reference, and compensate the switching device voltage drops and on-state resistances. Such compensation can be used to achieve an increase in the waveform quality of the converter. This is particularly useful in high-power, low supply voltage applications where a low switching frequency is used. The DC-Link voltage balancing capability of the method removes the requirement for additional control loops to actively balance the DC-Link voltage on each H-Bridge, simplifying the control structure. The proposed modulation technique has been validated through the use of simulation and extensive experimental testing to confirm its effectiveness.